(untitled) (Archives of Mechanics - Test, 2007)
The incompressible viscous steady flow through a helical pipe of circular cross-section rotating at a constant angular velocity about the center of curvature is investigated numerically to examine the combined effects of rotation (Coriolis force), torsion and curvature (centrifugal force) on the flow. The flow depends on the Taylor number Tr=[equation], the Dean number Dn=[equation], the torsion parameter β0=[equation] and the dimensionless curvature of the duct δ, where a is the radius of the helical pipe, ΩT the angular velocity, μ the viscosity, v the kinematic viscosity, G the constant pressure gradient along the pipe axis and β0 - a parameter related to the torsion τ and curvature δ. When ΩT>0, the rotation is in the direction in which the Coriolis force produces the curvature effect. When ΩT<0, the rotation is in the direction in which the Coriolis force exhibits an opposite effect to that of curvature. The calculations are carried out for -500 ≤ Tr ≤ 500, 1500 ≤ Dn ≤ 2000 (large Dean number), 0≤ β0 ≤ 0.4 and 0 < δ ≤ 0.2. The total flux through the duct has a sharp peak at a negative Tr.